Study of the Kinetics Adsorption of Organic Pollutants on Modified Cellulosic Polymer Using Ultraviolet-Visible Spectroscopy - Djamila Ghemati; Djamel Aliouche (Journal of Spectroscopy)
We report a study on the formation of the complex acrylamidomethylated-β-cyclodextrin, then on the grafting on cellulosic polymer. The grafting is initiated by ceric ions Ce(IV) and confirmed by infrared spectroscopy analysis (FTIR). Scanning electron microscopy (SEM) analysis was carried out to evaluate properties of structure and surface of grafted polymers. The experiments of the study of adsorption of balance of phenol and hydroquinone and a reactive dye, acid dyes, and cationic dyes using ultraviolet-visible microscopy were made in aqueous solutions for 24 hours at different pH. Our results indicate formation of a permanent chemical bond between β-cyclodextrin and polymers material. The cellulosic polymers can effectively be modified without significant change in the structural properties. Then, the results of organic pollutants adsorption in aqueous medium show the aptitude of the polymer modified to fix the phenol derivatives and synthetics dyes and used in the processing industrial liquid waste. The differences in adsorption capacities may be due to the effect of dye structure. The negative value of free energy change indicated the spontaneous nature of adsorption.